2017
DOI: 10.1021/acsinfecdis.7b00110
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy-Based Sandwich Immunoassays for Multiplexed Detection of Zika and Dengue Viral Biomarkers

Abstract: Zika and dengue are mosquito-borne diseases that present similar nonspecific symptoms but possess dramatically different outcomes. The first line of defense in epidemic outbreaks are rapid point-of-care diagnostics. Because many outbreaks occur in areas that are resource poor, assays that are easy to use, inexpensive, and require no power have become invaluable in patient treatment, quarantining, and surveillance. Paper-based sandwich immunoassays such as lateral flow assays (LFAs) are attractive as point-of-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 52 publications
(81 reference statements)
1
100
0
1
Order By: Relevance
“…Schifferli et al reported a gold nanostar (Au NS)-based LFA platform (Fig. 14), with the SERS limit of detection of 0.72 ng/mL of ZIKV NS1 and 7.67 ng/mL of DENV NS1 [192]. Nano Res.…”
Section: Plasmonic Paper Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Schifferli et al reported a gold nanostar (Au NS)-based LFA platform (Fig. 14), with the SERS limit of detection of 0.72 ng/mL of ZIKV NS1 and 7.67 ng/mL of DENV NS1 [192]. Nano Res.…”
Section: Plasmonic Paper Devicesmentioning
confidence: 99%
“…2018, 11(10): 5439-5473 Reproduced with permission from Ref. [192], © American Chemical Society 2017.…”
Section: Plasmonic Paper Devicesmentioning
confidence: 99%
“…The assay run time was optimized to 9 min and 20 min (Table 1) including sample preparation and loading. Until now the Zika NS1 levels in Zika-infected patients were still largely unknown/variable, whereas approximately 15 μg/mL Dengue NS1 can be found for Dengue-infected patient's serum after two days of infection [12,22]. Based on that, we have analyzed 2000.0, 1000.0, 500.0, 250.0, 125.0, and 62.5 ng/mL Zika NS1 spiking on plasma to perform M-ELISA on-chip (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…IgG and IgM antibodies are produced in the human body at the later stage of the infection (four to seven days), this makes them inapt for early stage detection. In contrast, NS1 antigen with a similar structure has been considered for highly sensitive, specific early stage detection for different flaviviruses previously [9][10][11][12][13][14]. There are currently numerous POC devices that detect ZIKV by using NS1 as a biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…The buffer solution was 1 l of 1x PBS with 1 mM MgCl2. The Raman peak due to Zika was around 1590 cm -1 [34] and [35].…”
Section: (B) One Could Resolve Individual Zika Viruses On Goldmentioning
confidence: 99%